Postcolonial Study on Guest by Camus in the lens of Homi Ke Bhabha - Raouf Aminzadeh; Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shiva Zaheri Birgani (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
The aim of this study is to discuss use of Postcolonial Study on Guest by Camus in the lens of Homi Ke Bhabha. The result of this study shows that The Arab was "imposing on him a kind of brotherhood he understood well but refused to accept in the particular circumstances," Daru believes (80). Due to the control Daru wields over the Arab as his 'transport' to the police and the political context of the region, the two have significant contrasts that make for a difficult friendship to form. The human connection, on the other hand, is undeniable, since the two sharing a place led to the formation of "an odd alliance," as Daru describes it